Influences Of Transition In Age-Education Structure And Internal Migration On The Labour Market In Brazil - Friedrich de Lima Amaral, Ernesto; Gonçalves Rios-Neto, Eduardo Luiz; E. Potter, Joseph (Informe GEPEC, 2000)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> This study develops a methodology that incorporates internal migration dynamics into models that estimate the impact of demographic and education transitions on the age-education earnings profiles of Brazilian workers over time. Techniques to estimate the level and pattern of migration were integrated. Findings follow initial hypothesis, and indicate that the negative impact of cohort size on earnings is even more negative than estimates that did not take into account population flows. These methodological strategies can be applied to further studies when new data become available, as well as to other countries with the availability of migration data.